Head and Neck Cancer in Hadhramout-Yemen : A Five Years Experience in Hadhramout Cancer Centre - Badheeb, Ahmed Mohamed (Author) مؤلفين آخرين: Bahannan, Abd Alrahman A. (Co-Author), Ba-amir, Abu bakir A. (Co-Author (مجلة الأندلس للعلوم الاجتماعية والتطبيقية, 2023)
Objective: To describe the pattern and distribution of head and neck cancers among patients registered at Hadhramout Cancer Centre in Al-Mukalla city. Patients and Methods: This study was conducted retrospectively to describe the pattern and distribution of head and neck cancers among patients registered at the Hadhramout Cancer Centre, in Al-Mukalla, for the period from January 2006 to December 2011. Data was collected using Can-Reg program and statistacally analyzed by computer SPSS program version 18. Results: The study included 202 patients with head and neck cancers, 132 were males (65.3%) and 70 were females (34.7%), with male to female ratio of 2:1. The mean age was 51.52 years (range: 41-60 years). The most common sites in this study are nasopharynx (42.6%), followed by larynx (13.4%) and tongue (12.9%). In males, the top three cancers are nasopharyngeal (51%), laryngeal (20%) and tongue cancers (14%), while the top three among females were nasopharyngeal (54%), gum (14.29%) and tongue (10%). The most common histopathological type is the squamous cell carcinoma (47.5%) followed by nasopharyngeal cancers type I, II, III (41.7%) and others (10.8%). Conclusions: Nasopharyngeal cancers were the most frequent HNC in Hadhramout Sector. Squamous cell carcinoma was the most common histopathology. Our results generally indicate that the pattern of our cases bear similarities with the Arab' data with some differences from the other parts of Yemen that necceciate further evaluation.